The Originality of Meister Eckhart’s Understanding of God - Vannier, Marie-Anne (Medieval mystical theology, 2025)
The way Eckhart talks about God can be disconcerting. He uses paradox and apophatism, but this is because of his experience of God, which made him realize that he is beyond the categories attributed to him. This is why the Thuringian explains that God is beyond God, beyond being. He is in himself bubbling. The term Deity would seem more appropriate to describe him, but here again, this term is inadequate. He is an outpouring of love and a constant invitation to divine filiation.